Seasonal Pattern of Endo-β-Mannanase Activity During Germination of Jeffersonia dubia, Exhibiting Morphophysiological Dormancy - Young Hyun Kwon; Seung Youn Lee; Yong Ha Rhie (Plants)
Morphophysiological dormancy (MPD) is considered one of the most primitive dormancy classes among seed plants. While extensive studies have examined the occurrence of endo-β-mannanase in seeds with physiological dormancy (PD) or non-dormancy, little is known about the activity of this enzyme in seeds with MPD. This study aimed to investigate the temporal and spatial patterns of endo-β-mannanase activity during dormancy break and germination. The research focused on Jeffersonia dubia, a species with deep simple MPD, by monitoring its morphological and biochemical characteristics under natural field conditions. Seeds were buried in the field and exhumed monthly over a year. Key parameters measured included germination, embryo elongation, endosperm weakening, and endo-β-mannanase activity in the exhumed seeds. Scanning electron microscopy was employed to observe structural changes in the endosperm. For the first three months after burial in May, endo-β-mannanase activity was undetectable, and the underdeveloped embryo exhibited minimal elongation. Starting in September, the embryo began to grow, accompanied by increased endo-β-mannanase activity in the micropylar endosperm. Erosion of the endosperm cell wall was observed in the lateral regions surrounding the embryo, whereas the micropylar endosperm showed no obvious signs of collapse or damage. The increase in enzyme activity coincided with moderate temperatures and a corresponding increase in embryo length. During the winter months, embryo elongation ceased for 2–3 months, and enzyme activity declined. However, as germination resumed in early March, enzyme activity increased again. This was followed by micropylar endosperm rupture and the completion of germination. The seasonal pattern of endo-β-mannanase activity observed in seeds with deep simple MPD was distinct from that of seeds with PD, MD, or non-deep MPD, highlighting the unique mechanisms underlying dormancy break and germination in J. dubia.